Development Of Portable Magnetic Clamping For Lathe Machine - Ab Wahab, Norfariza; Mohd Saleh, Afferry; Nordin, Abd Khahar; Tamin, Nor Fauzi; Ibrahim, Mohd Azimin; Ahmad, Suziana; Abdul Hadi, Dayanasari (Asian Research Publishing Network (ARPN), 2018)
Chuck is a device used to clamp any material that operates with the turning of the machine and it is connected to the headstock spindle of the lathe. However, the limitation is that the thickness of the workpiece must not be less than the area of clamping on the chuck. In this a new magnetic clamping for attaching and detaching the workpiece on the chuck and is able to clamp small and thin workpieces is developed. The chuck is made by using mild steel and has a few intercepts with brass. Magnetic mechanism is placed in the chuck. Several cutting processes were done with the convectional chuck and the magnetic clamping on a different thickness of workpiece. Next, all the workpieces were tested with several parameters on specimen and perform surface roughness testing to compare and finalize the effectiveness of the magnetic clamping. From the obtained result, the use of the magnetic clamping produces much better result of surface roughness on thin workpiece. Thus, using magnetic clamping as the clamping method for thin workpiece is much effective in turning machine.